Considerations on wrongful conviction based on forensic evidence: analysis by the Innocence Project, the National Registry of Exoneration and mechanisms for reducing forensic errors - Aline de Araújo Lourenço; Erick Simões da Camara e Silva (Revista Brasileira de Direito Processual Penal, 2021)
This article aims to analyze the relationship between expert evidence and wrongful convictions. It is a topic that is still little explored in Brazil, but with a wide debate in the USA. For this reason, it is used as the basis of the American model to answer the following questions: 1) What are the main American associations and databases related to the reversals of wrongful convictions? 2) What are the reflexes of the American approach in United Kingdom, Canada and Brazil? 3) How do expert evidence relate to wrongful convictions? 4) Are there criteria applicable to expert evidence that can be implemented in Brazil in order to reduce the chance of expert errors and misinterpretation by the judges? It is expected to present the point and the counterpoint in the use of expert evidence, to address the merits of associations that seek to reverse wrongful convictions and to suggest criteria to improve the way the experts dialogue with the judges.